A computationally efficient approach for calculating galaxytwo-point correlations. Issue 1 (7th July 2018) - Demina, Regina; Cheong, Sanha; BenZvi, Segev; Hindrichs, Otto
ABSTRACT: We developed a modification to the calculation of the two-point correlation function commonly used in the analysis of large-scale structure in cosmology. An estimator of the two-point correlation function is constructed by contrasting the observed distribution of galaxies with that of a uniformly populated random catalogue. The assumption that the distribution of random galaxies in redshift is independent of angular position allows us to replace pair-wise combinatorics with fast integration over probability maps. The new method significantly reduces the computation time while simultaneously increasing the precision of the calculation. Also, it only requires cosmological parameters at the last and least computationally expensive stage, which allows for faster exploration of the parameter space.